The Perfect Wife (A Jessie Hunt Psychological Suspense Thriller-Book One) - Blake, Pierce (Lukeman Literary, 2018)
Criminal profiler in training (and newlywed) Jessie Hunt, 29, discovers that dark secrets lurk in her new suburban town; when a body turns up dead, she finds herself caught in the crosshairs of her newfound friends, her husband's secrets, her serial killer caseload-and the secrets of her own dark past. In THE PERFECT WIFE (A Jessie Hunt Psychological Suspense Thriller-Book One), Criminal profiler-in-training Jessie Hunt is sure she's finally put the darkness of her childhood behind her. She and her husband, Kyle, just moved from a cramped downtown Los Angeles apartment into a Westport Beach mansion. Kyle's promotion has them swimming in money. And Jessie is on the verge of getting her Master's degree in forensic psychology, the last step in her dream of becoming a criminal profiler. But soon after their arrival, Jessie begins to notice a series of strange developments. The neighbors-and their au pairs-all seem to be hiding secrets. The mysterious yacht club Kyle is desperate to join is rife with cheating spouses, and with troubling rules of its own. And the notorious serial killer being held at the psychiatric hospital where Jessie is completing her degree seems to know more about her life than is normal-or safe. As her world starts to unravel, Jessie begins to question everything around her-including her own sanity. Has she truly uncovered a disturbing conspiracy buried within a sunny, wealthy Southern California beach town? Does the mass murderer she's studying really somehow know the origin of her private nightmares? Or has her tortured past finally come back to claim her? A fast-paced psychological suspense thriller with unforgettable characters and heart-pounding suspense, THE PERFECT WIFE is book #1 in a riveting new series that will leave you turning pages late into the night.
Keywords: Dobrodružství, napětí, thrillery; Krimi, detektivky